The 1-Hour Plasma Glucose: Common Link Across the Glycemic Spectrum - Bergman, Michael (Frontiers in Endocrinology, 2021)
Evidence from populations at risk for type 1 diabetes, type 2 diabetes or gestational diabetes substantiates the 1-hour plasma glucose as a sensitive alternative marker for identifying high-risk individuals when ß-cell function is relatively more functional. An elevated 1-hour plasma glucose could therefore diagnose dysglycemia and risk for complications across the glycemic spectrum. Reducing the 2-hour oral glucose tolerance test to 1-hour would reduce the burden on patients, likely reduce costs, and enhance its accessibility in practice while increasing sensitivity of detecting dyglycemia across the glycemic spectrum.